2015
DOI: 10.1007/s11547-014-0477-x
|View full text |Cite
|
Sign up to set email alerts
|

MRI findings of olivary degeneration after surgery for posterior fossa tumours in children: incidence, time course and correlation with tumour grading

Abstract: Our results demonstrate that olivary degeneration, with or without hypertrophy, is a relatively frequent consequence of posterior fossa surgery, particularly in children treated for high-grade tumours. Knowledge of this condition can prevent misdiagnoses and unnecessary investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…The etiology of CP was not explored in relation to motor planning, despite the fact that its impact on motor function has been established [120][121][122][123][124][125][126][127][128][129][130][131][132]. This is further supported by studies on other pediatric populations which have shown that damage to certain neurological networks is associated with motor planning deficits in children with tumors [133,134] or in children with neurodevelopmental disorders [135,136]. In addition, the results in bilateral tasks cannot be compared to those of unilateral tasks as both types of tasks rely on different neural networks [137,138].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of CP was not explored in relation to motor planning, despite the fact that its impact on motor function has been established [120][121][122][123][124][125][126][127][128][129][130][131][132]. This is further supported by studies on other pediatric populations which have shown that damage to certain neurological networks is associated with motor planning deficits in children with tumors [133,134] or in children with neurodevelopmental disorders [135,136]. In addition, the results in bilateral tasks cannot be compared to those of unilateral tasks as both types of tasks rely on different neural networks [137,138].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is of particular importance in neoplastic etiologies of HOD, such as described in our patient, as the new area of hypertrophy should not be confused for a tumoral lesion. The abnormality may be either unilateral or bilateral depending on the location of the lesion [ 10 ]. On MRI, HOD is described as a non-contrast enhancing T1 isointense lesion and a T2/FLAIR hyperintense lesion restricted to the ION [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…HOD represents a diagnostic challenge, particularly in cases involving neoplastic processes, as it may be confused with tumor metastasis or recurrence. The neurosurgical literature concerning HOD is limited, particularly in pediatric patients [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these primary causes, surgical manipulation of the posterior fossa is a well-known cause of subsequent HOD (Uchino et al, 1993;Phatouros and McConachie, 1998;Tsui et al, 1999;Harter and Davis, 2004;Akar et al, 2008;Hornyak et al, 2008;Gatlin et al, 2011;Yun et al, 2013;Tartaglione et al, 2015). Tartaglione et al (2015) reviewed the imaging findings in 58 children after surgery for posterior fossa tumors and found T2 signal changes in 33% of the cases and olivary enlargement in 36% of them. The changes were visible between 1 and 6 months after surgery with a tendency to decrease and becoming faint after 12 months.…”
Section: Discussionmentioning
confidence: 99%